2020
DOI: 10.1111/os.12817
|View full text |Cite
|
Sign up to set email alerts
|

Functional Comparison of Horizontal Mattress Suture VersusFree‐Edge Suture in the All‐Inside Arthroscopic Broström–Gould Procedure for Chronic Lateral Ankle Instability

Abstract: Objective: To compare the clinical outcomes of horizontal mattress suture vs free-edge suture in the all-inside arthroscopic Broström-Gould procedure. Methods: This retrospective cohort study included 68 chronic lateral ankle instability (CLAI) patients who underwent either a horizontal mattress suture or a free-edge suture all-inside arthroscopic Broström-Gould procedure from January 2014 to January 2017. Patients were divided into two groups based on the suture fashion during the all-inside arthroscopic Bros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…At a median follow-up of 6 years, significant improvements of the VAS, AOFAS, and Tegner scores were recorded in both groups. The arthroscopic modified Broström procedure with microfracture should be considered a reasonable method for CLAI patients with OLTs [ 41 ]. The modified Broström procedure and microfracture are a viable surgical option for the patient with CLAI and OLTs [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…At a median follow-up of 6 years, significant improvements of the VAS, AOFAS, and Tegner scores were recorded in both groups. The arthroscopic modified Broström procedure with microfracture should be considered a reasonable method for CLAI patients with OLTs [ 41 ]. The modified Broström procedure and microfracture are a viable surgical option for the patient with CLAI and OLTs [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The exercise participation rate of the two-anchor group (69.2%) was signi cantly higher than that of the oneanchor group (36.1%). Li et al [10] treated 51 patients with CAI (20 cases with one-anchor and 31 cases with two-anchor) with horizontal mattress suture in ABG. After at least 2 years of follow-up, AOFAS in the two groups were not statistically signi cant (90 ± 9 vs 91 ± 10).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the modi ed Broström procedure for ATFL repair assisted by ankle arthroscopy has been widely used and veri ed in biomechanics and clinical practice [5][6][7][8][9][10]. Many studies have reported encouraging results using single anchors [11,[16][17][18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations